Perceived Social Support and Work Motivation: The Mediating Role of Happiness in the Workplace - Susi Maria; Muhammad Rasyid Abdillah; Helwen Heri (SAINS ORGANISASI, 2022)
This study aims to explain the relationship between perceived social support and work motivation. In particular, this study uses the mechanism of happiness at work as a psychological mechanism that underlies the relationship between the two variables. By involving respondents who work as State Civil Apparatus (ASN) and Non-State Civil Apparatus in several local government institutions in one of the provinces in Indonesia and using SEM-PLS analysis, this study found that perceived social support had an effect on employee motivation. Furthermore, this study found that happiness at work mediates the relationship between perceived social support and employee motivation